French-Speaking Universities in Sub-Saharan Africa : A Critical Impasse - (:unkn) unknown (My University, 1993)
Administrators of French-speaking sub-saharan African universties are faced with a crule dilemna : with the passing years, their dwindling budgets have made it increasingly difficult for them to guarantee the proper functionning of their etablishments ; hence a decline in the level of competence of graduates and in research standards. At the same time, some studies show that unit costs are too high ant that higher education receives an inordinate amount of educational funding. They recommend that the squeeze on university budgets be sustained and tightened.The prmary aim of this article is to provide evidence to support these two seemingly contradictory assessments. It is true that while French-speaking universities in sub-Saharan Africa are short of funds, they still manage to spend too much ; however, it is equality true taht solutions to this problem exist and that strategies compatible with both observations can be found.
Keywords: African Research